Educator Sexual Misconduct: A Statutory Analysis - Abboud, Mia J. (Criminal justice policy review, 2020)
Educator sexual misconduct is a problem that has gained increased attention because of the high-profile cases reported by the news media. Yet, the diversity in state law regarding this offense remains somewhat unexplored. In this article, we compare and evaluate state statutory provisions regarding educator sexual misconduct; our focus is on what constitutes educator sexual misconduct, and what penalties are provided for offenders. As such, we explore the differences and similarities in statutory provisions across states in terms of the definition of child sexual assault, the age of consent, the penalties for various types of sexual misconduct perpetrated by teachers, and any requirement for registration as sex offenders. Our findings indicate that though the number of applicable statutes has almost doubled since 2010, there remains a wide variety in the definition and penalties included in those laws, and 21 states have not chosen to enact a specific law at all.